A class-room with a "view" : Net-based strategies to promote intercultural education - Raffaghelli, Juliana E.; Richieri, Cristina (Proceedings of the International Conference on Networked Learning, 2010)
Can the net become a place suitable for promoting intercultural education? Which elements are crucial to achieve this goal? There is strong agreement on the fact that the Internet represents a metaphor for a place or environment that has social significance in identity building processes (Turkle, 1996), as well as being a cultural environment promoting virtual citizenship and virtual communities (Rheingold, 1993) which, in time, can become formal learning communities capable of generating effective learning (Palloff & Pratt, 1999; Rovai, 2002b). Lately, some attention has been paid to the design of an interculturally sensitive virtual learning place, which can promote further intercultural learning (Rollin & Harrap, 2005; Bélisle, 2007; Rutheford & Kerr, 2008). The participated construction of a virtual working/learning space (VWLS) aimed at supporting a project of international cooperation on intercultural education among Turkey, Slovenia and Italy is described in this article. A case study is presented as a springboard for the discussion of net-based strategies to be included within an intercultural approach to education. The project was set up with the aim of showing how a VWLS can give support to dimensions that are the kernel of intercultural education, from the motivation to share one’s own cultural identity (constituted by symbols, icons, music, etc.), to collaboration across frontiers. Furthermore, a possible new concept of intercultural education is presented, as the current idea of it needs to be redefined on the basis of the growing networked learning phenomenon. If VWLS becomes meaningful, it will expose participants to an enlarged cultural context, different to but also comprehensive of their own original context. The process of making sense of what is new could impact on a new dimension of intercultural learning which takes place on the net, a place where there are no frontiers and reality is virtual.